2016
DOI: 10.1007/s11892-016-0712-z
|View full text |Cite
|
Sign up to set email alerts
|

The Affordable Care Act and Diabetes Diagnosis and Care: Exploring the Potential Impacts

Abstract: This article reviews available data on the implications of the Affordable Care Act (ACA) for the diagnosis and care of type 2 diabetes. We provide a general overview of the major issues for diabetes diagnosis and care, and describe the policies in the ACA that affect diabetes diagnosis and care. We also estimate that approximately 2.3 million of the 4.6 million people in the USA with undiagnosed diabetes aged 18–64 in 2009–2010 may have gained access to free preventive care under the ACA, which could increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 54 publications
0
18
1
Order By: Relevance
“…In addition, states with the highest proportion of undiagnosed diabetes often did not expand Medicaid, further contributing to possible omitted variable bias, although cases of undiagnosed diabetes were not examined. 48 Although this was mitigated by including interaction terms for race that changed differentially over time, this may have been insufficient (B Zeldow and LA Hatfield, unpublished data, November 27, 2019). Second, the sample size of Medicaid-eligible residents with diabetes could have Note: Boldface indicates statistical significance for difference-in-difference estimator: being in expansion state during the postexpansion period.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, states with the highest proportion of undiagnosed diabetes often did not expand Medicaid, further contributing to possible omitted variable bias, although cases of undiagnosed diabetes were not examined. 48 Although this was mitigated by including interaction terms for race that changed differentially over time, this may have been insufficient (B Zeldow and LA Hatfield, unpublished data, November 27, 2019). Second, the sample size of Medicaid-eligible residents with diabetes could have Note: Boldface indicates statistical significance for difference-in-difference estimator: being in expansion state during the postexpansion period.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Unfortunately, states with higher rates of undiagnosed diabetes were less likely to expand Medicaid, potentially compounding decades-long systemic disparities in diabetes care quality and serving as a negative confounder in our study. [4] Paradoxically, if efforts to repeal or weaken insurance market protections for patients with pre-existing conditions succeed, patients who have been diagnosed with diabetes because of Medicaid expansion may have greater restrictions for treatment than if Medicaid had never expanded, because these patients will now have a pre-existing medical condition.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In 2009-2010, 23% of adults ages 18-64 with diagnosed diabetes were uninsured -roughly 3.5 million Americans. [4] Of these patients, 1.5 million met income qualifications for expanded Medicaid coverage. A recent study comparing insurance among adults age 18-64 with diabetes in 2016 versus 2009 found a statistically significant 5% increase in coverage.…”
Section: Introductionmentioning
confidence: 99%
“…The Affordable Care Act has resulted in increased access to care for many individuals with diabetes with an emphasis on health promotion and disease prevention (43). As mandated by the Affordable Care Act, the Agency for Healthcare Research and Quality developed a National Quality Strategy based on the triple aims that include improving the health of a population, overall quality and patient experience of care, and per capita cost (44,45).…”
Section: Strategies For System-level Improvementmentioning
confidence: 99%